2012
DOI: 10.5812/aapm.4300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Pregabalin Premedication on Post-Operative Pain in Laparoscopic Gastric Bypass Surgery

Abstract: BackgroundPost-operative pain and the administration of opioids to relieve it, is considered to be one of the important issues in surgery wards. This issue is even more significant in obese patients, because of the side effects of opioids. Pregabalin is an analog of gamma aminobutyric acid (GABA) which can be effective in dealing with post-operative pain.ObjectivesThis study will consider the effect of oral pregabalin in relieving the pain of obese patients after gastric bypass surgery.Patients and MethodsIn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 23 publications
6
50
1
2
Order By: Relevance
“…Alimian M. et al 16 and Alimian M. et al 17 in their respective studies also observed that postoperative pain intensity level were lower in patients who received oral 300 mg Pregabalin an hour before surgery. Opioid consumption were also lower in the Pregabalin group than the placebo group.…”
Section: Discussionmentioning
confidence: 88%
“…Alimian M. et al 16 and Alimian M. et al 17 in their respective studies also observed that postoperative pain intensity level were lower in patients who received oral 300 mg Pregabalin an hour before surgery. Opioid consumption were also lower in the Pregabalin group than the placebo group.…”
Section: Discussionmentioning
confidence: 88%
“…Paracetamol, NSAID, or COX-2 inhibitors, gabapentinoids, ketamine and alpha-2 agonists, when used individually, have all been shown to reduce postoperative opioid requirement and improve pain relief. [10][11][12][13][14] Different combinations of these agents, together with local anaesthetic infiltration of the wounds, have been reported for bariatric surgery, as discussed below.…”
Section: Importance Of Reducing Postoperative Opioid Use In Obese Patmentioning
confidence: 99%
“…Outcomes on pain intensity levels were consistently lower and nausea/ vomiting decreased in the study group. No opioid use or effect on mobilization was assessed [6] (Table 2). …”
Section: Premedicationmentioning
confidence: 99%